Machinery Usage and Productivity in Manufacturing: Firm-Level Matter in Developing Countries - Nguyen, Manh Hung; Vu, Hoang Dat; Thanh, Tran Thi Mai; Pham, Sy An (Ital Publication, 2025)
This study examines the determinants of machinery usage and its relationship with productivity outcomes among Vietnamese manufacturing firms, using nationally representative panel data from 2010 to 2019. A multinomial logit model and panel regressions with first- and second-differences reveal substantial heterogeneity in machinery choices, reflecting differences in firm size, ownership, and sectoral contexts. Medium and large enterprises tend to use computer-controlled machinery and are more likely to exhibit positive associations with labor productivity, although these effects often diminish over time. In contrast, micro and small firms remain reliant on handheld tools and show mixed or short-lived productivity gains. Foreign-invested enterprises demonstrate more consistent productivity benefits from advanced machinery than state-owned firms. These findings suggest that sustained productivity improvements require more than technological upgrades alone. The study highlights the potential importance of complementary investments – such as workforce development, managerial capacity, and institutional support – for fostering inclusive and effective machinery usage. These insights may inform targeted policy efforts aimed at narrowing technology gaps across heterogeneous firms in developing economies.